PENDIDIKAN KARAKTER PADA SEKOLAH DASAR DI PONDOK PESANTREN DALAM PEMBENTUKAN KEDISIPLINAN, TANGGUNG JAWAB, DAN KEMANDIRIAN SISWA - Miftahul Jannah (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
An Najah Sekolah Dasar Tahfiz Quran Terpadu (SDTQ-T) Boarding School, Cindai Alus Martapura has more complex instrument than character education process instrument in school or Islamic school because it has uniqueness, where students are schooling and staying in the same environment so that it can form very well and conducive environment for educational and character building process especially in discipline, responsibility and independence.The objectives of the study are to describe and analyze: (1) Character Education Strategy in building students’ discipline, responsibility, and independence in An Najah SDTQ-T Boarding School, Cindai Alus Martapura. (2) Character Education Model in building students’ discipline, responsibility, and independence Model in An Najah SDTQ-T Boarding School, Cindai Alus Martapura. (3) Implication of Character Education Model in building students’ discipline, responsibility, and independence in An Najah SDTQ-T Boarding School, Cindai Alus Martapura.This research uses qualitative approach with case study type. The data collection techniques are interview, observation and documentation. The data are analyzed qualitatively with analysis model of Miles and Huberman. The research results show: (1) Character Education Strategy in building students’ discipline, responsibility and independence in An Najah SDTQ-T Boarding School, Cindai Alus Martapura are: Emphasizing in awareness, model/example, spontaneous activities, warning, environment conditioned, regular activities, and integrated discipline.(2) Character Education Model in building students’ discipline, responsibility and independence in An Najah SDTQ-T Boarding School, Cindai Alus Martapura are habitual, dgiving example, developing discipline, and giving reward and punishment, CTL, conducting education with boarding school system. (3) Implication of Character Education Model in building students’ discipline, responsibility, and independence are: correct conduct in teaching and learning activities, students’ fidelity, students’ quality, confidence and achievement, and most of the students achieve minimum score of 70, the increase of discipline, responsibility, and independence graphic every year in students’ score reports.